Kierunki ewolucji prawa wyborczego w Polsce a demokracja partycypacyjna - Stelmach, Andrzej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
One highly significant phenomenon demonstrating that public life is becoming increasingly democratic is provided by the formal and material guaranty of the citizens’ political participation. Legitimization of power is an important issue. For the sake of simplicity, it may be said that one political option or another has won the elections. Under Polish conditions, an electoral victory means that a given party won more votes than any other. But by no means does it say that this party has won the support of a majority of voters. Poland has been ruled by the parties that have won anything from 20.41% of the votes, as the Democratic Left Alliance (SLD) did in 1993, to the 41.51% Civic Platform (PO) won in 2007. This shows that power has been exercised by political parties that have not won the approval of a majority of voters. The picture looks even worse when the support rulers enjoy is not measured in terms of approval expressed by voters, but in terms of absolute values, i.e. the proportion of all citizens entitled to vote. The legitimization of power is extremely low when analyzed from this perspective. In the best case it amounts to 21.89% obtained by the victorious party, and 26.58% of all entitled to vote won by the coalition formed by the victorious parties to rule after the elections. Thus it is difficult to talk about democratic governance, understood as the rule of the majority. It should rather be concluded that the ruling parties are those that have won the largest support, which only means that they have collected more votes than any other political power taking part in the same elections. Understood in this way, power is not exercised on behalf of a majority, but by the best organized minority.
Directions of electoral law evolution in Poland and participatory democracy
Keywords: electoral law; Poland; democracy; prawo wyborcze; Polska; demokracja